Находки оружия и конской сбруи на пригородных усадьбах Ольвии - Папанова, В.А.; Ляшко, С.Н. (Материалы по археологии Северного Причерноморья, 2015)
In the first decade of the twenty-first century in suburban farmstead of Shyroka Balka 6 (Broad Hollow) (oikos), Shyroka Balka 7 (Broad Hollow) (chorion) and in the family burial area of oikos residents (excavated in the 90s ХХ century) the weapon (a fragment of the iron mahayry blade, bronze and iron arrowheads, lead bullet for a sling, etc.) and parts of harness were found. We would like to also emphasize that weapons are rare findings in the settlements of Olbia chora. Analysis of the ceramic material allowed to clarify the dating of the found weapons.